The study of cancer patients’ distress - Lunevičiūtė, Ūla; Masteikienė, Egidija (Acta medica Lituanica, 2014)
Background. Distress of cancer patients is often left unnoticed and it induces various problems: it is harder for patients to adjust to the illness, the quality of life is poorer, it causes much distress for the team of oncologists. 1 year before in the VU Institute of Oncology the Distress Thermometer was started to be used for all patients in the hospital. Purpose. To explore distress prevalence and features of cancer patients’ in the hospital. Participants and methods. There were 488 participants. The Distress Thermometer (DT) was used to evaluate distress of the participants. DT consists of a Likert type scale from 0 to 10 that assesses the strength of experienced distress, and a problem list that includes practical, family, emotional, spiritual and physical problem groups. Results. The mean score of distress of all participants was 3.47 (SD = 2.47). 82% of participants pointed from 0 to 5 scores, 18% of participants indicated from 6 to 10 scores. There was a statistically significant corellation between the distress score and the number of problems (r = 0.43, p
Keywords: distress; Distress Thermometer; cancer patients